Hi all,
How can I solve this?
I tried with log_a (b) - log_a (c) = log_a (b/c) but the solution is (13+5x)/(x^2+5x+4)>=0 ...how is this possible?
Thanks in advance
Okay, as you say, $\displaystyle log_{1/3}(x^2- 9)- log_{1/3}(x^2+ 5x+ 4)\ge 0$ is the same as $\displaystyle log_{1/3}\left(\frac{x^2- 9}{x^2+ 5x+ 4}\right)\ge 0$.
Further $\displaystyle log_a(x)\ge 0$, for any a< 1, if and only if $\displaystyle x\le 1$. That is, your inequality is the same as $\displaystyle \frac{x^2- 9}{x^2+ 5x+ 4}\le 1$.
Subtracting 1 from both sides, $\displaystyle \frac{x^2- 9}{x^2+ 5x+ 4}- 1= \frac{x^2- 9- (x^2+ 5x+ 4)}{x^2+ 5x+ 4}= \frac{-5x- 13}{x^2+ 5x+ 5}\le 0$.
Now, multiply both sides by -1.